Low-chromium aluminum-chromium refractory material for lining of rock wool furnace and preparation method of low-chromium aluminum-chromium refractory material

By using low-chromium aluminum-chromium refractory materials, combined with high-temperature in-situ mulle petrochemical reaction and chemical replacement to generate gas, the problem of insufficient thermal shock stability and corrosion resistance of rock wool furnace lining materials is solved, and the material is realized Densification and high temperature performance improvement.

CN119462102AActive Publication Date: 2025-02-18WUHAN UNIV OF SCI & TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411653545.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing rock wool furnace lining materials have poor thermal shock stability and insufficient corrosion resistance under high temperature and strong mechanical erosion, which is difficult to meet the production needs of rock wool cup furnaces.

Method used

Using low-chromium aluminum-chromium refractory materials, a dense material structure is formed by mixing corundum particles and fused zirconium mullite particles, combining high-temperature in-situ mullite reactions between rosylic and zircon, and a dense material structure is formed through a phosphoric acid solution and Chemical replacement of Si powder produces gas, achieving fine porosity and high-temperature performance improvement of the material.

Benefits of technology

It improves the thermal shock stability and corrosion resistance of the rock wool furnace lining material, enhances the density and sintering performance of the material, reduces the thermal expansion coefficient, and is suitable for high temperature and intermittent working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462102A_ABST
    Figure CN119462102A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rock wool furnaces, in particular to a low-chromium aluminum-chromium refractory material for a rock wool furnace lining and a preparation method of the low-chromium aluminum-chromium refractory material. The preparation method comprises the following steps: S1, stirring and mixing corundum particles and fused zirconium mullite particles to obtain a premixed particle material; s2, the corundum fine powder, the chromium concentrate fine powder, the andalusite fine powder and the zirconite fine powder are mixed and ground together until the particle size is smaller than or equal to 65 micrometers, and premixed fine powder is obtained; s3, mixing the premixed granular material and the premixed fine powder material to obtain a premixed material; s4, sequentially adding Si powder and aluminum silicate fibers into the premix, and mixing to obtain a mixture; s5, adding a phosphoric acid solution into the mixture, stirring and mixing, adding into a mold for vibration molding, naturally curing, and drying to obtain a green material; and S6, the green body material is subjected to high-temperature heat preservation for a period of time. The refractory material prepared by the invention is environment-friendly, high in sintering density, good in thermal shock resistance, small in thermal expansion coefficient and strong in erosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rock wool furnaces, and in particular to a low-chromium aluminum-chromium refractory material for a rock wool furnace lining and a preparation method thereof. Background Art

[0002] Rock wool is a fiber material made of basalt as the main material, with slag, dolomite, limestone and other raw materials added for tempering. It is obtained through processes such as melting, blowing, and cotton collection and molding. It is commonly used for heat insulation, thermal insulation, and sound insulation in buildings and industrial scenes. It is non-flammable, durable, and lightweight. With the implementation and promotion of the country's dual carbon goals, the demand for rock wool products is increasing.

[0003] Commonly used kilns for producing rock wool include kiln pools, electric furnaces, and cupolas. Kiln pools have high investment and production costs, consume a lot of energy, and are currently less used; electric furnaces are a type of rock wool production equipment that has emerged in recent years, and have advantages in energy conservation and emission reduction, improving production efficiency, and utilizing solid waste; while cupolas use fossil fuels such as coke and natural gas as heat sources, and the raw materials are usually natural minerals or slag in blocks with a particle size of 30 to 80 mm, and the operating temperature of the oxidation zone is usually above 1500°C. Cupolas are currently the most common equipment for melting rock wool, accounting for more than 90% of domestic rock wool production equipment ( Si Fuyin, Sun Shibing, Qiu Zhiming, etc. Comparison of rock wool melting in cupola and electric melting furnace[J]. Glass, 2024, 5:44-50 ).

[0004] Taking the cupola as an example, the rock wool cupola is a vertical smelting furnace. The raw materials and coke are added from the top, and gradually heated, reduced, and melted before moving downward. During the movement, the blocky raw materials and coke are fully mixed and rubbed against the lining, causing wear of the cupola lining. At the same time, in order to fully improve the thermal efficiency of the cupola, the furnace usually has hot air preheating, oxygen-enriched air combustion, electromagnetic / mechanical stirring devices, etc., which will produce strong mechanical scouring on the cupola lining. In addition, since the raw materials for producing rock wool are usually natural ores, slag and solid waste, in recent years, due to the requirements of energy conservation and carbon reduction, the preparation of rock wool products from hot molten slag has become a hot spot for industrial transformation. The composition of liquid slag is difficult to accurately control, which requires the addition of SiO2, Al2O3, etc. for tempering during the production process. In short, the raw materials for rock wool smelting are from a wide range of sources, have mixed components, high acidity, and poor uniformity, which cause strong erosion to the lining. The hot molten slag ladle feeding is intermittent, so the rock wool cupola is an intermittent working equipment. Some cupolas have water-cooled coils outside the furnace wall, which makes the rock wool lining material bear strong thermal shock. Therefore, the rock wool furnace lining material should have good mechanical properties, slag erosion resistance and thermal shock stability ( Sun Shibing, Tian Yingliang, Han Jixian, et al. Development status of rock wool manufacturing in my country and production carbon reduction approaches[J]. Journal of Beijing University of Technology, 2022, 48(3): 306-311 ).

[0005] At present, there is no consensus at home and abroad on the selection of refractory materials for rock wool furnace lining. Usually, quartz refractory materials, carbon-containing refractory materials, non-oxide composite materials and aluminum refractory materials are selected based on the experience of iron-making cupolas.

[0006] For example, quartz refractory materials have good resistance to acidic slag erosion, but the source of rock wool smelting raw materials is wide, and the alkalinity range of rock wool slag is wide, so quartz refractory materials are difficult to be widely used; in addition, quartz refractory materials have poor thermal shock stability. For rock wool furnaces that are fed with slag bags and work intermittently, they are very susceptible to thermal shock and peeling.

[0007] Carbon-containing refractory materials and non-oxide composite materials can also be used as rock wool cupola lining materials. Patent CN114956794 B discloses a method for preparing a corrosion-resistant rock wool electric furnace lining material, which is obtained by mixing and stirring silicon carbide, white corundum, silicon oxynitride, boron carbide, metal aluminum powder, and a resin binder. However, the rock wool furnace is a high-temperature kiln that works intermittently in an air atmosphere. Carbon-containing and silicon carbide composite materials are prone to oxidation, and the service life of the furnace lining will be shortened due to oxidation.

[0008] Aluminum refractory materials mainly include corundum refractory materials, high aluminum refractory materials and aluminum-chromium refractory materials. Aluminum refractory materials have good chemical stability, high strength, good anti-scouring performance, and strong anti-corrosion performance against acidic slag and alkaline slag. However, aluminum refractory materials also have the disadvantage of poor thermal shock stability, and the use effect on rock wool furnaces is still not ideal. (Sun Fan, Li Xiaoyan, Liu Xiaobin. Introduction to refractory materials and furnace construction process for EC&S cupola[J]. China Foundry Equipment and Technology, 2018, 53(4): 97-101) .

[0009] Among aluminum-chromium refractories, Cr2O3 has a very low solubility in slags of different basicities, so it has good resistance to slag erosion. Aluminum-chromium refractories also have excellent high-temperature performance and erosion resistance, so aluminum-chromium refractories are one of the ideal choices for rock wool furnace lining refractories. Aluminum-chromium refractories are usually prepared with corundum and chrome green as raw materials. Its main chemical composition is aluminum oxide and chromium oxide, with fewer impurities. Because aluminum-chromium bricks have good high-temperature strength and resistance to slag erosion, they are mostly used in hazardous waste incinerators, glass kiln regenerators, water-coal slurry gasification furnaces, non-ferrous metal smelting and other harsh service environments. Patent CN 118812249 A discloses a method for preparing a furnace lining of rock wool using corundum and Cr2O3 as raw materials. According to different temperature zones in the furnace, SiO2, Fe2O3, CaO, and MgO are used as additives, and high-chromium corundum castables with different Cr2O3 and Al2O3 contents are set as the furnace lining to obtain a rock wool furnace lining with good resistance to fly ash erosion. This method uses a variety of additives to reduce the strength and load softening temperature of the furnace lining, thereby reducing the deformation and anti-scouring ability of the furnace lining. Summary of the invention

[0010] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to propose a low-chromium aluminum-chromium refractory material for rock wool furnace lining and a preparation method thereof. The method has a simple process and does not require special instruments or equipment for processing. The prepared low-chromium aluminum-chromium refractory material for rock wool furnace lining is environmentally friendly, has high sintering density, good thermal shock stability, small thermal expansion coefficient, and strong corrosion resistance.

[0011] A method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining of the present invention comprises the following steps:

[0012] S1. Mixing corundum particles and fused zirconium mullite particles in a mass ratio of 100:(10-15) to obtain a premixed particle material;

[0013] S2. Mix and grind the corundum fine powder, chromium concentrate fine powder, andalusite fine powder and zircon fine powder in a mass ratio of 100:(12-18):(13-16):(5-8) to a particle size of ≤65 μm to obtain a premixed fine powder;

[0014] S3, mixing the premixed granular material and the premixed fine powder material in a mass ratio of 100:(55-65) to obtain a premix;

[0015] S4, adding 0.8-1.2% of Si powder and 1.2-1.5% of aluminum silicate fiber by weight of the premix to the premix in sequence, and mixing to obtain a mixture;

[0016] S5, adding a phosphoric acid solution accounting for 6.5-7.2% of the mass of the mixture to the mixture, stirring and mixing, adding the mixture to a mold for vibration molding, and drying after natural curing to obtain a green material;

[0017] S6. Keeping the green material at high temperature for a period of time to obtain a low-chromium aluminum-chromium refractory material for rock wool furnace lining.

[0018] Furthermore, in step S6, the temperature is kept at 1520-1570° C. for 8-10 hours.

[0019] Furthermore, the particle size of the corundum particles is 0.2-6 mm, wherein the particle material ratio of [0.2 mm-2 mm]: [3 mm-4 mm]: [5 mm-6 mm] is (10-15): (40-60): (15-20).

[0020] Furthermore, the particle size of the fused zirconium mullite particles is 2-5 mm, wherein the particle material ratio of [2 mm-3 mm]:[4 mm-5 mm] is 10:(2-3).

[0021] Furthermore, the particle size of the Si powder is ≤45 μm; and the Si content of the Si powder is ≥99.5%.

[0022] Furthermore, the diameter of the aluminum silicate fiber is 10 to 20 μm, and the length is 3 to 6 mm.

[0023] Furthermore, the concentration of the phosphoric acid solution is 1.5-2.5 mol / L.

[0024] A low-chromium aluminum-chromium refractory material for rock wool furnace lining prepared by the above-mentioned preparation method.

[0025] The beneficial effects of the present invention are:

[0026] (1) The present invention utilizes the high-temperature in-situ mullitization reaction of andalusite and zircon to improve the bonding of the matrix material and promote the densification of the material; and the SiO2 glass formed during the mullitization process forms a coating on the chromium-containing components, hindering the oxidation transformation of Cr2O3 in the chromium concentrate to a high-valent state, thereby eliminating the environmental risks of the chromium-containing components.

[0027] (2) The present invention utilizes the cross-distribution of corundum particles and fused zirconium mullite particles to form a continuous network skeleton to improve the bonding of particle components; at the same time, the particle size gradient and grade difference of the fine powder are utilized to improve the dispersion performance of the matrix fine particles, which is beneficial to the filling of the aggregate-matrix and effectively improves the density and sintering performance of the material.

[0028] (3) The present invention utilizes the chemical replacement of phosphoric acid solution and Si powder to generate gas, and realizes the miniaturization of the internal pores of the material through the bridging and drainage of aluminum silicate fibers. On the one hand, it reduces the porosity of the material, reduces the thermal expansion of the material, and improves the thermal shock stability of the material.

[0029] (4) The present invention utilizes the saturated solid solution of corundum and chromium concentrate in a high-temperature liquid medium to improve the grain boundary bonding strength of the aluminum-chromium solid solution, avoid the erosion of the material from the grain boundary by the slag, and further improve the corrosion resistance of the material.

[0030] The low-chromium aluminum-chromium refractory material for rock wool furnace lining prepared by the present invention has been tested:

[0031] Bulk density is 2.88~3.17g / cm 3 ; Apparent porosity 18.7~22.2% (GB / T2997-2015); Flexural strength retention rate after 5 thermal shock tests at 1100℃ air cooling is 78~85% (GB / T30873-2014); High temperature thermal expansion coefficient at 1600℃ is (6.3~6.8)×10 -6 / ℃(GB / T 7320-2008); 1600℃×3h static crucible method slag resistance test after corrosion index 3.3~5.7%(GB / T 8931-2007).

[0032] Therefore, the process of the present invention is simple and does not require special instruments or equipment for processing; the prepared low-chromium aluminum-chromium refractory material for rock wool furnace lining is environmentally friendly, has high sintering density, good thermal shock stability, small thermal expansion coefficient, and strong corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM microscopic photograph of a low-chromium aluminum-chromium refractory material sample for rock wool furnace lining prepared in Example 1;

[0034] Figure 2 This is a SEM microscopic photograph of the low-chromium aluminum-chromium refractory material sample for rock wool furnace lining prepared in Example 1 after being eroded by rock wool. DETAILED DESCRIPTION

[0035] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0036] Example 1

[0037] A method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining, the specific steps are as follows:

[0038] S1. Add corundum particles and fused zirconium mullite particles into a planetary mixer at a mass ratio of 100:12, and mix for 6 to 8 minutes to obtain a premixed particle material;

[0039] S2. Add the corundum fine powder, chromium concentrate fine powder, andalusite fine powder and zircon fine powder into a roller mixer in a mass ratio of 100:12:14:8, mix and grind to a particle size of ≤65 μm, and obtain a premixed fine powder;

[0040] S3, adding the premixed granular material and the premixed fine powder material into a mixer at a mass ratio of 100:60, and mixing for 10 to 15 minutes to obtain a premix;

[0041] S4, adding 0.8% Si powder and 1.3% aluminum silicate fiber by weight of the premix to the premix, and mixing for 8 to 10 minutes to obtain a mixture;

[0042] S5, adding a phosphoric acid solution accounting for 7.2% of the mass of the mixture to the mixture, stirring for 5 to 8 minutes, adding the mixture to a mold for vibration molding, naturally curing for 10 to 12 hours, and drying at 100 to 110° C. for 8 hours to obtain a green material;

[0043] S6. Add the green material into a high temperature furnace and keep it at 1570° C. for 10 hours to obtain a low-chromium aluminum-chromium refractory material for rock wool furnace lining.

[0044] Figure 1 This is a SEM microscopic photo of a low-chromium aluminum-chromium refractory material sample for rock wool furnace lining. It can be seen that the material grains are fully grown, the organization structure is uniform, the grain size is large, and the combination is tight. The material has good density and sintering performance and can effectively resist the erosion of slag. There is no low-melting phase attachment filling between the grain boundaries, the solid-solid direct bonding strength is high, and fine pores can be found inside the grains in a dispersed distribution, which is conducive to improving the thermal shock stability of the material.

[0045] Figure 2 This is a SEM microscopic photo of a low-chromium aluminum-chromium refractory material sample for rock wool furnace lining after being corroded by rock wool. It can be seen that the corrosion reaction mainly occurs in the matrix part, and the corroded medium and the material body show obvious "interface stratification", indicating that the material has good resistance to the corrosive medium; in the matrix, the low-melting products produced by the corrosion are blocked and form a continuous and tight area, indicating that the overall structure of the material is intact after corrosion, without obvious cracking or peeling, and has good resistance to slag corrosion.

[0046] The low-chromium aluminum-chromium refractory material for rock wool furnace lining prepared in this embodiment was tested:

[0047] Bulk density is 3.17 g / cm 3 ; Apparent porosity 18.7% (GB / T2997-2015); Flexural strength retention rate after 5 thermal shock tests at 1100℃ air cooling is 85% (GB / T30873-2014); High temperature thermal expansion coefficient at 1600℃ is 6.6×10 -6 / ℃(GB / T 7320-2008); 1600℃×3h static crucible method slag resistance test after corrosion index 3.3%(GB / T 8931-2007).

[0048] Example 2

[0049] A method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining, the specific steps are as follows:

[0050] S1. Add corundum particles and fused zirconium mullite particles into a planetary mixer at a mass ratio of 100:15, and mix for 6 to 8 minutes to obtain a premixed particle material;

[0051] S2. Add the corundum fine powder, chromium concentrate fine powder, andalusite fine powder and zircon fine powder into a roller mixer in a mass ratio of 100:15:13:6, mix and grind to a particle size of ≤65 μm, and obtain a premixed fine powder;

[0052] S3, adding the premixed granular material and the premixed fine powder material into a mixer at a mass ratio of 100:55, and mixing for 10 to 15 minutes to obtain a premix;

[0053] S4, adding 1.2% Si powder and 1.5% aluminum silicate fiber by weight of the premix to the premix, and mixing for 8 to 10 minutes to obtain a mixture;

[0054] S5, adding a phosphoric acid solution accounting for 6.5% of the mass of the mixture to the mixture, stirring for 5 to 8 minutes, adding the mixture to a mold for vibration molding, naturally curing for 10 to 12 hours, and drying at 100 to 110° C. for 10 hours to obtain a green material;

[0055] S6. Add the green material into a high temperature furnace and keep it at 1520° C. for 9 hours to obtain a low-chromium aluminum-chromium refractory material for rock wool furnace lining.

[0056] The low-chromium aluminum-chromium refractory material for rock wool furnace lining prepared in this embodiment was tested:

[0057] Bulk density is 3.12g / cm 3 ; Apparent porosity 19.4% (GB / T2997-2015); Flexural strength retention rate after 5 thermal shock tests at 1100℃ air cooling is 78% (GB / T30873-2014); High temperature thermal expansion coefficient at 1600℃ is 6.3×10 -6 / ℃(GB / T 7320-2008); 1600℃×3h static crucible method slag resistance test after corrosion index 5.7%(GB / T 8931-2007).

[0058] Example 3

[0059] A method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining, the specific steps are as follows:

[0060] S1. Add corundum particles and fused zirconium mullite particles into a planetary mixer at a mass ratio of 100:10, and mix for 6 to 8 minutes to obtain a premixed particle material;

[0061] S2. Add the corundum fine powder, chromium concentrate fine powder, andalusite fine powder and zircon fine powder into a roller mixer at a mass ratio of 100:18:16:5, mix and grind to a particle size of ≤65 μm, and obtain a premixed fine powder;

[0062] S3, adding the premixed granular material and the premixed fine powder material into a mixer at a mass ratio of 100:65, and mixing for 10 to 15 minutes to obtain a premix;

[0063] S4, adding 1.0% Si powder and 1.2% aluminum silicate fiber by weight of the premix to the premix, and mixing for 8 to 10 minutes to obtain a mixture;

[0064] S5, adding a phosphoric acid solution accounting for 6.6% of the mass of the mixture to the mixture, stirring for 5 to 8 minutes, adding the mixture to a mold for vibration molding, naturally curing for 10 to 12 hours, and drying at 100 to 110° C. for 12 hours to obtain a green material;

[0065] S6. Add the green material into a high temperature furnace and keep it at 1550° C. for 8 hours to obtain a low-chromium aluminum-chromium refractory material for rock wool furnace lining.

[0066] The low-chromium aluminum-chromium refractory material for rock wool furnace lining prepared in this embodiment was tested:

[0067] The bulk density is 2.88 g / cm 3 ; Apparent porosity 22.2% (GB / T2997-2015); Flexural strength retention rate after 5 thermal shock tests at 1100℃ air cooling is 81% (GB / T30873-2014); High temperature thermal expansion coefficient at 1600℃ is 6.8×10 -6 / ℃(GB / T 7320-2008); 1600℃×3h static crucible method slag resistance test after corrosion index 4.2%(GB / T 8931-2007).

[0068] For matters not mentioned above, the prior art applies.

[0069] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining, characterized in that: The steps include: S1. Mixing corundum particles and fused zirconium mullite particles in a mass ratio of 100:(10-15) to obtain a premixed particle material; S2. Mix and grind the corundum fine powder, chromium concentrate fine powder, andalusite fine powder and zircon fine powder in a mass ratio of 100:(12-18):(13-16):(5-8) to a particle size of ≤65 μm to obtain a premixed fine powder; S3, mixing the premixed granular material and the premixed fine powder material in a mass ratio of 100:(55-65) to obtain a premix; S4, adding 0.8-1.2% of Si powder and 1.2-1.5% of aluminum silicate fiber by weight of the premix to the premix in sequence, and mixing to obtain a mixture; S5, adding a phosphoric acid solution accounting for 6.5-7.2% of the mass of the mixture to the mixture, stirring and mixing, adding the mixture to a mold for vibration molding, and drying after natural curing to obtain a green material; S6. Keeping the green material at high temperature for a period of time to obtain a low-chromium aluminum-chromium refractory material for rock wool furnace lining.

2. The method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining according to claim 1, characterized in that: In step S6, the temperature is kept at 1520-1570° C. for 8-10 hours.

3. The method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining according to claim 1, characterized in that: The particle size of the corundum particles is 0.2-6 mm, wherein the particle material ratio of [0.2 mm-2 mm]: [3 mm-4 mm]: [5 mm-6 mm] is (10-15): (40-60): (15-20).

4. The method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining according to claim 1, characterized in that: The particle size of the fused zirconium mullite particles is 2-5 mm, wherein the particle material ratio of [2 mm-3 mm]:[4 mm-5 mm] is 10:(2-3).

5. The method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining according to claim 1, characterized in that: The particle size of the Si powder is ≤45 μm; the Si content of the Si powder is ≥99.5%.

6. The method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining according to claim 1, characterized in that: The aluminum silicate fiber has a diameter of 10 to 20 μm and a length of 3 to 6 mm.

7. The method for preparing a low-chromium aluminum-chromium refractory material for rock wool furnace lining according to claim 1, characterized in that: The concentration of the phosphoric acid solution is 1.5-2.5 mol / L.

8. A low-chromium aluminum-chromium refractory material for rock wool furnace lining prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A corrosion-resistant rock wool furnace lining material and its preparation method

    CN114956794B

  • Furnace body lining layer for preparing rock wool by recycling fly ash and application of furnace body lining layer

    CN118812249A

  • Aluminum-chromium-silicon fireproof material

    CN103755361A

  • High-performance bauxite-chromite refractory matter, as well as preparation method and application thereof

    CN109320219A

  • Preparation method of dry material for intermediate frequency furnace lining for stainless steel smelting

    CN111875396A